Application of the Film-Based Sociodrama Method to Improve Speaking Skills - Mariyadi, Mariyadi (Mimbar Sekolah Dasar, 2023)
Students require speaking to communicate and process information. However, their speaking skills are still low, as they are still, for example, unable to produce their arguments, ideas, or feelings communicatively. This study aims to determine the application of the film-based drama method in improving speaking skills of grade VI elementary school students in the Indonesian Language subject in Sekarjati 1 Public Elementary School. The subjects of this classroom action research (CAR) were 11 students from grade VI. Data were collected using observation and tests. The data analysis technique was descriptive quantitative. Results showed that the application of the film-based sociodrama can improve speaking skills of grade VI elementary school students in the Indonesian Language subject. The implementation of the classroom action research resulted in an increase of 73% from cycle I (27%) to cycle II (100%). The method can be a solution for teachers to improve students' speaking skills.